FLUCTUACIONES ESTACIONALES DE MICROARTROPODOS EDAFICOS BAJO ESPECIES VEGETALES EN LA RESERVA NACIONAL RIO CLARILLO (REGION METROPOLITANA, CHILE) - Covarrubias, Rene (Acta Entomológica Chilena, 2022)
Microarthropods were sampled along an annual cycle, in the National Reserve “Rio Clarillo” (Metropolitan Región, Chile). The sampling design discriminated two factors, namely time and plant species; for the latter factor the soils were chosen, under Quillaja saponaria, Persea lingue, Lithraea caustica and Puya chilensis, all of them beeing “Characteristic” species of different vegetational subunits of the Reserve and, anyway, most representative of the local vegetation. Microarthropods were extracted by means of Berlese-Tullgren funnels. The whole mass of taxa obtained was separated after their frequencies in the samples, in different groups. For each group data were given of their respectives densities (X and s). The more interesting group of higher frequencies was formed by Cryptostigmatid, Actinedid (or Prostigmatid), Tarsonemid and Gamasid mites, also Díptera larvae. Each taxa of this subset was submitted to a two way anova analysis, based on their individual densities. All of them showed significant variations for the time factor and all, but Oribatida, changed significantly in regards to the plant species factor. Also was described and analyzed the possible effect of a series of microclimatic elements, on the densities of these 5 high frequency taxa. The elements taken into account were, air temperatures (average, minimal, maximal), soil temperatures at four depths, relative humidity, evaporation and total amount of rainfall. Also the fall of the leaves of Persea lingue was recorded along the annual cycle and put into relation to the other factors.